Characterization of the multiple components of Acanthopanax Senticosus stem by ultra high performance liquid chromatography with quadrupole time‐of‐flight tandem mass spectrometry. Issue 3 (29th December 2015) - Sun, Hui; Liu, Jianhua; Zhang, Aihua; Zhang, Ying; Meng, Xiangcai; Han, Ying; Zhang, Yingzhi; Wang, Xijun
Abstract : Acanthopanax Senticosus Harms . has been used widely in traditional Chinese medicine for the treatment of chronic bronchitis, neurasthenia, hypertension and ischemic heart disease. However, the in vivo constituents of the stem of Acanthopanax Senticosus remain unknown. In this paper, ultra high performance liquid chromatography with electrospray ionization quadrupole time‐of‐flight mass spectrometry and the MarkerLynx TM software combined with multiple data processing approach were used to study the constituents in vitro and in vivo. The aqueous extract from the Acanthopanax Senticosus stem and the compositions in rat serum after intragastric administration were completely analyzed. Consequently, 115 compounds in the aqueous extract from Acanthopanax Senticosus stem and 41 compounds absorbed into blood were characterized. Of the 115 compounds in vitro, 54 were reported for first time, including sinapyl alcohol, sinapyl alcohol diglucoside, and 1‐ O ‐sinapoyl‐β‐d ‐glucose. In the 41 compounds in vivo, 7 were prototype components and 34 were metabolites which were from 21 components of aqueous extract from Acanthopanax Senticosus stem, and the metabolic pathways of the metabolites were elucidated for first time. The results narrowed the range of screening the active components and provided a basis for the study of action mechanism and pharmacology.